Cold plasma treatment to improve germination and enhance the bioactive phytochemical content of germinated brown rice - Sittidet Yodpitak (2019)
© 2019 Elsevier Ltd The changes in the bioactive phytochemicals of six cultivars of Thai germinated brown rice (GBR) were monitored in parallel to those of cold plasma-treated GBR (PGBR). After treatment with the optimal plasma conditions, the germination percentage, root length, and seedling height measurements of the most sensitive rice cultivar increased by 84%, 57%, and 69%, respectively. For all of the rice cultivars, there were no significant differences in the antioxidant activities of the GBRs and PGBRs. Conversely, higher contents of γ-oryzanols were observed in the PGBR group than in the GBR group during the 2-day germination period. Certain cultivars in the PGBR group reached their maximum values for total phenolic compounds, total vitamin E, certain simple phenolics, phytosterols, triterpenoids, and anthocyanins one day earlier than the same values for GBR. In contrast, the concentrations of 2-acetyl-1-pyrroline in both the GBR and PGBR samples were reduced significantly with increased germination time.